2004
DOI: 10.1007/s11661-004-0073-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and thermodynamic calculation of the phase equilibria in the Cu-Sn and Cu-Sn-Mn systems

Abstract: The phase equilibria in the Cu-rich portion of the Cu-Sn binary and Cu-Sn-Mn ternary systems have been determined using the diffusion-couple method, differential scanning calorimetry (DSC), high-temperature electron diffraction (HTED), and high-temperature X-ray diffraction (HTXRD) techniques. The present experimental results on the binary Cu-Sn system show the presence of the two-stage, second-order reaction in the bcc-phase region, rather than a two-phase equilibrium between the disordered bcc (A2) and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 26 publications
5
40
0
Order By: Relevance
“…Therefore, this transformation is most likely attributed to a second-order ordering reaction of the peritectic phase occurring during solidification. These measurements favor the Cu-Sn phase diagram of Liu et al [2]. …”
Section: Cu-268 Wt% Snsupporting
confidence: 71%
See 3 more Smart Citations
“…Therefore, this transformation is most likely attributed to a second-order ordering reaction of the peritectic phase occurring during solidification. These measurements favor the Cu-Sn phase diagram of Liu et al [2]. …”
Section: Cu-268 Wt% Snsupporting
confidence: 71%
“…A close comparison with a microsegregation model that included back-diffusion in the primary a-solid phase allowed us to validate successfully the heat flow model. SPTA on Cu-Sn alloys have shown that the CuSn phase diagram recently reinvestigated in Liu et al's review [2] is the most reliable. Obviously, the thermal analysis method developed here can be used for other metals and alloys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a clear phase identification, concentration measurements have also been carried out using a microprobe. Finally, the observed solidification paths have been compared with the Cu-Sn phase diagram of Liu et al [2].…”
Section: Introductionmentioning
confidence: 99%